Optimalisasi TOGA Berkelanjutan Workshop Minyak Serai Sebagai Upaya Menambah Value Tanaman Serai di Desa Dadapan, Kecamatan Kendal, Kabupaten, Ngawi, Jawa Timur - Masyekha, Masyekha Ahmad Firmansyah; Wulandari, Nurul Via; Widiyana, Novi; Fajriyah, Ella Nur; Taufiq, Amal (Institut Agama Islam Negeri Kerinci, 2025)
The utilization of Family Medicinal Plants (TOGA) as a source of traditional medicine has not been fully optimized within the context of economic empowerment in Dadapan Village. One of the potential plants in TOGA is lemongrass (Cymbopogon sp.), which contains high-value lemongrass oil. This study aims to examine a community empowerment approach based on local potential in Dadapan Village, Kendal Subdistrict, Ngawi Regency, East Java, through a workshop program on lemongrass oil production as a form of sustainable TOGA optimization. The method used refers to the Asset-Based Community Development (ABCD) theory approach, which focuses on five main principles: Discovery, Dream, Design, Define, and Destiny. Through local asset mapping, needs identification, and participatory intervention design, this program encourages the creation of added value for the community by utilizing existing resources. The results of the program implementation show an increase in the community’s technical knowledge of lemongrass oil distillation processes, as well as a growing collective initiative to transform TOGA into a productive economic resource. Thus, the ABCD approach has proven effective in building independence based on local potential while promoting the transformation of TOGA from a merely consumptive function to a productive one. The implications of this activity are not only ecological and economic but also support social sustainability through the strengthening of community capacity in a participatory and sustainable manner.